Overpressure characteristics and geological origin of the paleogene in Baiyun Sag, Pearl River Mouth Basin - Xiong, Ting; Cheng, Leli; Guo, Dongming; Guan, Lijun; Jiang, Qiangtao; Zhangming, Hu; Yin, Senlin; Chen, Gongyang (Frontiers in Earth Science, 2023)
The accurate understanding of the origin of overpressure is the basis of formation pressure research and the core work of determining the distribution of formation pore pressure in drilling design. The deep water area of Baiyun Sag in the Pearl River Mouth Basin in the northern margin of the South China Sea has been proved to be a hydrocarbon rich depression. In recent years, overpressure has been encountered in the middle and deep layers, but the geological origin of the overpressure in the deep water area are still unclear. Therefore, the pore pressure profile of the Baiyun Sag was evaluated using the data of drilling and seismic velocity, and the relationship between overpressure and the generation mechanism was established. Most of the surrounding and shallow strata of Baiyun Sag show normal pressure, while the middle and deep strata generally show overpressure, with the maximum pressure coefficient up to 1.55. The overpressure zone mainly develops from the middle of Zhujiang Formation to the upper member of Enping Formation. The mudstone resistivity and density values of the two typical Wells deviated from the normal trend. The density showed a constant trend with the increase of depth, while the resistivity showed a certain degree of reversal. The upper layer of the overpressure zone showed abnormally high resistivity values, corresponding to the overgland and transition zone formed by high carbonate content. There is no obvious increase of porosity in the overpressured sandstone strata of Baiyun sag, which does not have the characteristics of undercompaction. The velocity in the overpressure section of the two Wells varies greatly, and the density is basically unchanged or slightly decreased. It is concluded that the overpressure is caused by fluid expansion from hydrocarbon-generation. The large-scale and long-term fluid expansion caused by hydrocarbon generation and expulsion of source rocks provides the power source for the formation of overpressure in Baiyun sag. The distribution of effective source rocks has a controlling effect on the distribution range of overpressure. The tight sandstone strata in the Zhuhai, Wenchang and Enping formations become the cover layer of the overpressure system in the longitudinal direction.